Analysis of DeepL Application as an Alternative Media for Translating Academic Assignments - Firda, Firda Hariroh; Zainuddin; Hamdani, Beny (IKIP Siliwangi, 2025)
This study aims to analyze the use of the DeepL as an alternative media for translating academic assignments of English language students. This study uses a qualitative-descriptive method, obtained through observations, interviews, and documentation. The objects of this research were 6 English language students as active users of the DeepL application. The study results indicate that the DeepL application can significantly help students translate academic assignments faster, more accurately, and efficiently, although there are limitations in translating certain terms. In addition, the use of the DeepL application also affects students' understanding and abilities in the English context. This study concludes that DeepL is an effective tool to support and assist in translating students' academic assignments. Still, its use must be supported by a competent linguistic understanding to avoid translation errors.